2006
DOI: 10.5551/jat.13.329
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Effects of Pravastatin, Atorvastatin, and Simvastatin on Insulin Secretion from a β-cell Line, MIN6 Cells

Abstract: In addition to the prevention of cardiovascular diseases by lowering plasma LDL cholesterol, recent studies suggest that statins could have some impact on insulin action. To estimate the direct effects of statins on insulin secretion from pancreatic -cells, MIN6 cells were treated with pravastatin, simvastatin, or atorvastatin. Basal insulin secretion at low glucose concentration was unexpectedly increased at very high doses of simvastatin or atorvastatin after 24-and 48-hour incubation. Insulin secretion at h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
43
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 22 publications
8
43
0
3
Order By: Relevance
“…Yada et al reported that simvastatin, but not pravastatin, inhibits glucose-induced insulin secretion through a blockade of L-type Ca 2 channels in isletcells 22) . In addition, atorvastatin was reported to impair insulin secretion 23) . The suppressive effect on insulin secretion might be due to the cytotoxicity of lipophilic statins for -cells or activation of SREBPs by statins.…”
Section: Discussionmentioning
confidence: 99%
“…Yada et al reported that simvastatin, but not pravastatin, inhibits glucose-induced insulin secretion through a blockade of L-type Ca 2 channels in isletcells 22) . In addition, atorvastatin was reported to impair insulin secretion 23) . The suppressive effect on insulin secretion might be due to the cytotoxicity of lipophilic statins for -cells or activation of SREBPs by statins.…”
Section: Discussionmentioning
confidence: 99%
“…Atorvastatin and simvastatin have been shown to decrease glucose uptake in adipocyte cell lines (26) and insulin sensitivity (27), respectively. Simvastatin and atorvastatin have been shown to decrease insulin secretion in b-cells (28). The inhibition of isoprenoid synthesis may explain some of the observed dysglycemic effects of statins (26).…”
Section: Plausibilitymentioning
confidence: 99%
“…Pourquoi n'y a-t-il pas alors plus d'exemples citant l'efficacitĂ© des statines dans la prĂ©vention du DT2 ? Trois Ă©tudes indĂ©pendantes ont montrĂ© qu'un traitement d'Ăźlots isolĂ©s de rat ou de cellules MIN-6 par des statines lipophiles (simvastatine, atorvastatine et lovastatine) est toxique sur la cellule ïą, alors que la pravastatine, hydrophile, est sans effet [28][29][30]. Des Ă©tudes interventionnelles chez l'homme, ciblant spĂ©cifiquement le rĂŽle des statines sur la fonction ïą cellulaire, seront nĂ©cessaires pour dĂ©terminer la nature exacte de ce lien.…”
Section: Quelle Pertinence Chez L'homme ?unclassified